## integral of csc^2

### The integral of csc^2x, also written as ∫csc^2x dx, requires a trigonometric identity and a substitution to solve

The integral of csc^2x, also written as ∫csc^2x dx, requires a trigonometric identity and a substitution to solve.

Let’s start by recalling the trigonometric identity for csc^2x:

csc^2x = 1 + cot^2x

Now, let’s rewrite the integral using this identity:

∫csc^2x dx = ∫(1 + cot^2x) dx

We can split this integral into two parts:

∫1 dx + ∫cot^2x dx

The integral of 1 dx is simply x + C, where C represents the constant of integration.

For the integral of cot^2x dx, we need to make a substitution. Let’s use u = cotx.

To differentiate u with respect to x, we apply the chain rule: du/dx = -csc^2x.

Rearranging this equation, we get dx = -du/csc^2x.

Now, let’s substitute these values into the integral:

∫cot^2x dx = ∫(cot^2x)(-du/csc^2x)

Simplifying, we have:

∫cot^2x dx = -∫du

Since the integral of du is simply u + C, we can write:

∫cot^2x dx = -u + C

Substituting back u = cotx:

∫cot^2x dx = -cotx + C

Finally, integrating the two parts of the original integral:

∫csc^2x dx = x – cotx + C

Therefore, the integral of csc^2x is x – cotx + C, with C representing the constant of integration.

##### More Answers:

Step-by-Step Solution | Integration of sin(x) using SubstitutionHow to Find the Integral of Cos(x) Using Trigonometric Identity

Solving the Integral of sec^2(x) using U-substitution | Step-by-Step Guide and Answer